2022
DOI: 10.3390/jcm11071810
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Prognostic Score for Critical COVID-19 Derived from Patients without Comorbidities Performs Well in Unselected Patients

Abstract: We aimed to search for laboratory predictors of critical COVID-19 in consecutive adults admitted in an academic center between 16 September 2020–20 December 2021. Patients were uniformly treated with low-molecular-weight heparin, and dexamethasone plus remdesivir when SpO2 < 94%. Among consecutive unvaccinated patients without underlying medical conditions (n = 241, 49 year-old median, 71% males), 22 (9.1%) developed critical disease and 2 died (0.8%). White-blood-cell counts, neutrophils, neutrophil-to-lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…We used only clinical data and medical history since full laboratory investigations were not available for a large portion of patients included in the study. It is possible that known predictors of adverse outcomes, such as ferritin, lactate dehydrogenase, or neutrophil to lymphocyte ratio, could improve our models [ 40 ]. Even though we have data regarding the number of individual vaccine doses, we do not have information with regard to the distance from the last dose.…”
Section: Discussionmentioning
confidence: 99%
“…We used only clinical data and medical history since full laboratory investigations were not available for a large portion of patients included in the study. It is possible that known predictors of adverse outcomes, such as ferritin, lactate dehydrogenase, or neutrophil to lymphocyte ratio, could improve our models [ 40 ]. Even though we have data regarding the number of individual vaccine doses, we do not have information with regard to the distance from the last dose.…”
Section: Discussionmentioning
confidence: 99%
“…These data indirectly imply that women of premenopausal age were less likely to seek medical attention in a hospital setting, presumably due to less severe disease. Along the same lines, in a parallel study from our group in consecutive unvaccinated patients without underlying medical conditions, it was shown that the number of female patients was half than men across all age groups [56] . Unfortunately we were not able to directly prove that basal type I IFN responses could predict a more robust immune response during viral infection due to the study design; however it is counterintuitive that higher constitutive type I IFN responses are associated with more robust type I IFN and IL-6 responses during active infection.…”
Section: Discussionmentioning
confidence: 53%
“…For example, the existence of monoallelic vs. biallelic ACE2 and Toll-like receptor 7 genes on the X chromosome may help to explain the greater risk of COVID-19 infection in males compared to females (37). Several studies have reported laboratory parameters, such as eosinophils, lymphocytes, PLTs, immature granulocytes, ferritin and liver enzymes as biomarkers of poor outcomes in patients with COVID-19 (36,(38)(39)(40)(41)(42). Of note, only a few studies have evaluated laboratory data as biomarkers of poor outcomes in tocilizumab-treated patients with COVID-19 (29)(30)(31)(32)(33)(34)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%